Ungheria 1551-1552: nuovi possibili spunti sulle campagne imperiali contro il Turco tratti dal codice ambrosiano G 275 inf. - Carpentieri, Chiara Maria (Verbum – Analecta Neolatina, 2012)
This study focuses on the miscellaneous codex G 275 inf., which is kept in the Ambrosiana Library of Milan. This codex containsmore than seventy Italian and Latin documents which pertain to the Hapsburg campaigns between 1551 and 1552 — guided by the famous captain Giovanni Battista Castaldo — against the Turks in Hungary and in Transylvania. The aim of this study is to present the extraordinary cultural heritage handed down by this manuscript. After a physical description of the codex, its content is studied in a preliminary analysis; there are some documents written on behalf of important historical characters, such as Ferdinand I Hapsburg, Queen Elisabeth of Hungary, and Giovanni Battista Castaldo. In addiction, there are documents on various subjects, such as military instructions, notes, noblemen lists, etc. In conclusion, these documents seem really worthy of an in-depth study in order to find some unpublished texts which could help historians to improve the knowledge of 16th-century Hungarian history.